2004
DOI: 10.1200/jco.2004.06.123
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Palliative Radiotherapy (17 Gy per two fractions) in Advanced Non–Small-Cell Lung Carcinoma Is Comparable to Standard Fractionation for Symptom Control and Survival: A National Phase III Trial

Abstract: Our data indicate that protracted palliative TRT renders no improvement in symptom relief, HRQOL, or survival when compared with short-term hypofractionated treatment in advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
114
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 29 publications
11
114
0
2
Order By: Relevance
“…More than two third of patients with non-small cell lung cancer (NSCLC) presented with advanced stage (III and IV) [1]. The majority of patients with unresectable stage III NSCLC are unfit for radical chemoradiotherapy (CRT) either due to the presence of extensive intrathoracic disease, poor performance status or significant comorbidities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than two third of patients with non-small cell lung cancer (NSCLC) presented with advanced stage (III and IV) [1]. The majority of patients with unresectable stage III NSCLC are unfit for radical chemoradiotherapy (CRT) either due to the presence of extensive intrathoracic disease, poor performance status or significant comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…There have been 14 published randomized clinical trials evaluating the optimal hypofractionation regimen to palliate symptoms of advanced NSCLC, which are considerably less resource and time intensive [1,2,[5][6][7][8][9][10][11][12][13][14][15][16]. However there is still no consensus on which fractionation scheme should be used.…”
Section: Introductionmentioning
confidence: 99%
“…The palliative benefits reported in our trial are consistent with the reported literature subject to dose and fractionation. The level of benefit relative to the these studies may have been underestimated due to the short time interval from treatment completion to the final assessment of symptom benefit (Simpson et al, 1985;Macbeth et al, 1996;Sundstrom et al, 2004). In the MRC study (Macbeth et al, 1996), symptom response was assessed by the Rotterdam Symptom Checklist for the duration of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup who have good performance status, limited metastatic involvement and require palliation of local symptoms have been treated with various regimens of high-dose palliative radiotherapy (HDPR), ranging from 30 Gy in 10 fractions to 42 Gy in 15 fractions or equivalent (MRC Lung Cancer Working Party, 1992;Macbeth et al, 1996;Ball et al, 1997;Plataniotis et al, 2002;Kramer et al, 2003;Sundstrom et al, 2004). High-dose palliative radiotherapy has been shown to provide an excellent palliative benefit through the reduction of local symptoms in 80 -90% of patients, and also benefits in terms of global quality of life (QOL) (Schaafsma and Coy, 2000;Bezjak et al, 2002;Sundstrom et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation